USER SATISFACTION IN DIGITAL SCHOOL REPORTING: AN EMPIRICAL STUDY OF RDM QUALITY IN MADRASAH IBTIDAIYAH ACROSS MALANG CITY - Atief Aisyil Wi’am; Naila Faizah Salsabila; Prayudi Lestantyo (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the influence of system quality, information quality, and service quality on user satisfaction with the Madrasah Digital Report Card (RDM) at Madrasah Ibtidaiyah in Malang City. This study adopts DeLone and McLean’s Information System Success Model as its primary theoretical framework. The independent variables in this study are system quality, information quality, and service quality, while user satisfaction serves as the dependent variable. The research method employs a quantitative approach with a causal-associative research design. The sample consisted of 91 elementary madrasah teachers selected using purposive sampling. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics version 23. Validity, reliability, normality, and heteroscedasticity tests were conducted on the collected data, followed by t-tests, F-tests, and R². The results indicate that information quality and service quality have a positive and significant effect on user satisfaction, whereas system quality does not have a significant effect. These findings suggest that user satisfaction is influenced by the quality of the information produced and the quality of the services provided, rather than by the characteristics of the system quality itself. Therefore, improving information quality and service quality should be a priority in supporting the successful implementation of the Madrasah Digital Report Card.